Podnikatelský záměr rozvoje podniku - Čapek, Jiří (Vysoké učení technické v Brně. Fakulta podnikatelská, 2010)
Cílem této diplomové práce je navrhnout podnikatelský záměr pro rozvoj elektronického obchodu prodávajícího japonské kuchyňské nože. Teoretická část popisuje formy podnikání, způsob sestavování podnikatelského záměru a náležitosti založení elektronického obchodu. V analytické části je popsán současný stav obchodu Jakuno a situace e-komerce v České republice. Závěr práce se zabývá již samotným podnikatelským záměrem a předkládá svoje návrhy pro zlepšení výkonnosti podniku.

The goal of this master’s thesis is to suggest a business plan of development for e - shop expansion, that sells japanese kitchen knives. The theoretical part describes the forms of business, the method of composing a business plan and the requirements for establishing an e – shop. In the analytical part, the contemporary situation of the e – shop Jakuno is described and the situation of e-commerce in Czech Repulic as well. The conclusion of this thesis deals with the business plan itself and proposes its suggestions for improving the company efficiency.
Business Plan of Development
Keywords: Podnikatelský záměr; elektronický obchod; e – shop; e – komerce; japonské nože; Business plan; e – shop; e – commerce; japanese knives